COMPETITIVE INNOVATIVE STRATEGIES IN THE RESORT BUSINESS - Mendela, I.Ya.; Mendela Ye.М. (The actual problems of regional economy development, 2023)
The resort business is one of the most dynamic and changing industries, which requires constant adaptation to new trends and consumer demands. In this context, competitive and innovative marketing strategies become extremely important for the successful development of the resort business. With the emergence of new competitors, changing tastes of tourists and the development of technology, companies that cannot provide competitive and innovative marketing strategies quickly exit the market. Competitive, innovative marketing strategies in the resort business enable companies to attract new customers and retain existing ones to ensure a steady stream of profits and growth. This study is devoted to the study of competitive innovative marketing strategies that will allow companies in the resort sector to be successful and competitive in the market. This topic is understudied, as scientists study innovative strategies and their impact on the company's activities, but the resort business remains neglected. The purpose of the article is to reveal the role of competitive innovative marketing strategies in the resort business. The study shows that the development of general innovative marketing strategies will indicate the result of their implementation. Analysis of the main specific features of innovative activity in the resort business will ensure the generation of the main innovative marketing strategies. Researching various approaches to innovative marketing strategies in the resort business will indicate the focus on attracting new customers and increasing sales. The introduction of innovative activities of the resort enterprise will allow the enterprise to generate a competitive strategy for long-term development. The scientific novelty of the study consists in highlighting the specific features of innovative activity in the resort business, since innovative activity is an important tool for achieving a competitive advantage of a resort enterprise. The practical significance of the study is that its main provisions can be used in the practical activities of resort enterprises. Competitive and innovative marketing strategies are a very important element of the successful operation of resort enterprises. Under these conditions, it is natural to increase the interest of scientists and practitioners in marketing aspects in the process of researching competitive innovative marketing strategies in the resort business.